De la jerarquización funcional continua de los asentamientos a la discreta: el caso de Aragón - Bielza de Ory, Vicente (Geographicalia, 2017)
The dificulties in passing from a continuons to a discrete hierarchical model and the necessity of discrete hierarchies in territory arrangement are firsfty established. To achien un aragonese functional hierarchization we utilice Davies model, using 117 variables fiscal licences).From the continuons hierarchy of real centralities we arrive to a discrete hierarchy of the christallerian type through several steps: thresholds by the means of typified measures, metropolitan area municipal elimination, suppression at an elemental level of negative attraction idex, consideration of centrality mean increments to accept 'continuum' ruptures, chistering of hierarchical levels through improvement of the nearest-neighbour index.